MICROBIAL α-L-RHAMNOSIDASES: CLASSIFICATION, DISTRIBUTION, PROPERTIES AND PRACTICAL APPLICATION - N. V. Borzova; L. D. Varbanets (Biotechnologia Acta, 2023)
One of the important problems of current biotechnology is the usage of enzymes of microbial origin for destruction of poorly soluble compounds and synthesis of new drugs. In recent years a great deal of researchers’ attention has been given to such technologically promising carbohydrases as O-glycosylhydrolases catalyzing the hydrolysis of O-glycoside links in glycosides, oligo- and polysaccharides, glycolipids, and other glycoconjugates.